Experimental evidence of high tick infestation limiting chick growth and survival in a colonial seabird - Teresa Militão; Augustin Clessin; Amandine Gamble; José Pedro Granadeiro; Thierry Boulinier; Paulo Catry (Scientific Reports)
Abstract While numerous studies have established correlations between parasite load and negative effects on their hosts, establishing causality is more challenging because parasites can directly compromise host condition and survival or simply opportunistically thrive on an already weakened host. Here, we evaluated whether Ixodes uriae, a widespread seabird tick, can cause a decrease in growth parameters (body mass, bill length and growth rates) and survival of chicks of a colonially seabird, the black-browed albatross (Thalassarche melanophris) breeding on New Island (West Falkland). To investigate this, we daily removed the ticks from 28 randomly selected chicks during their first 14 days of life (treated chicks) and compared their growth and survival with 49 chicks of a control group. The tick load on control chicks correlated negatively with their body mass, growth rates and survival. Comparisons between treated and control chicks demonstrated that tick infestation depleted body mass and hampered the growth of control chicks. Treated chicks had a higher survival rate than control ones to fledgling age, but not to 14 days old, suggesting that the delayed higher mortality on control chicks was caused by the accumulation of sub-lethal effects of ticks. This study experimentally demonstrates that high tick infestation can cause reduced host growth and survival.